GREEN LEADERSHIP AND SUSTAINABLE BUSINESS PERFORMANCE: EVIDENCE FROM SOUTHEAST ASIAN SMEs - Abu Siri (Adisam Publisher, 2025)
This study aims to explore the relationship between green leadership and sustainable business performance in small and medium-sized enterprises (SMEs) in Southeast Asia through a literature review. In the context of increasing global pressure on environmental sustainability and social responsibility, SMEs are required to adopt a leadership model that is oriented not only toward economic profit but also toward environmental protection and social welfare. This study analyzes various relevant academic literature and empirical reports from the past decade to identify the strategic role of green leaders in driving sustainable innovation, resource efficiency, and improving corporate reputation. The findings indicate that green leadership is positively correlated with sustainable business performance through strengthening an environmentally friendly organizational culture, employee engagement in green initiatives, and increasing SME competitiveness in the regional market. This study also highlights the structural and cultural challenges faced by SMEs in Southeast Asia in consistently implementing green leadership principles. The implications of this research provide a conceptual basis for developing managerial strategies and public policies that support SMEs' transition to greener and more sustainable business practices.